Case Study : Restoran Nasi Ulam Cikgu / Samihah Mohamad Yusoff - Mohamad Yusoff, Samihah (2020)
For the project report, the first step is the general information of the company has been gathered and the information is gathered through the primary and secondary sources for example we interviewed the owner of Nasi Ulam Cikgu Restaurant and we also gathered information about Nasi Ulam Cikgu through the article through the internet. The second part is, specialized subject study which the objective of the project is to view background, organizational structure, products and services that have been provided in Nasi Ulam Cikgu Restaurant. Next, we study about the technology or system that have been used in Nasi Ulam Cikgu Restaurant and marketing strategy used by the company to promote their restaurant is really interesting and successful as Nasi Ulam Cikgu was the one of the restaurant that was really popular in Kelantan. Lastly we do some research about company financial and how they manage their financial to reach their goal. Goals indicate what a business unit wants to achieve. Strategy is an action plan for getting the goals. Every business must design a strategy for achieving its goals, consisting of a marketing strategy, and an effective management.